Study of Microbiological Quality and Antioxidant Activity Beras Kencur Drink with Heating Process - Sakina Yeti Kiptiyah; Eni Harmayani; Umar Santoso (Indonesian Food and Nutrition Progress, 2017)
Beras kencur drink is well known as Indonesian herbal drink made from kencur (Kaempferia galanga L.) mixed with other functional ingredients through minimally-processing. The aim of this research was to evaluate microbiological quality and determine antioxidant activity of beras kencur drink with blanching and pasteurization treatment. Five samples were subjected to microbiological analysis by total plate count (TPC). Furthermore, the variation of heat treatment is blanching (5 and 10 minutes) and pasteurization. The sample were evaluated for pH value, total dissolved solids, total microbial, antioxidant activity, total phenolic content, total flavonoid content, and ferric reducing power. The results showed that five samples of beras kencur drink had varied total microbial amount while the samples treated with blanching and pasteurization had lower total microbial number. Samples with blanching kencur 5 minutes, blanching kencur 10 minutes and pasteurization had antioxidant activity of 80,30 %RSA, 64,78 %RSA and 58,24 %RSA, respectively, total phenolic content 1747,17 mgGAE/L, 1610 mgGAE/L, and 1465,13 mgGAE/L, respectively, total flavonoid content of 169,49 mgEK/L, 160,36 mgEK/L, and 136,31 mgEK/L, and ferric reducing power -1186,92 mgAA/L, 960,50 mgAA/L, and 897,61 mgAA/L. Beras kencur drink with blanching and pasteurization process had lower total microbial number and can improve antioxidant activity.